Validity of the Systemic Lupus Erythematosus Disease Activity 2000-Glucocorticoid Index, its association with the Physician Global Assessment, and potential association with disease damage - Basma M. Medhat; Lobna A. Maged; Doaa A. Teleb; Sally S. Mohamed; Angie Y. Afifi; Dina M. T. Koptan; Walaa Abdelrahman; Dalia Dorgham; Eman Hany Elsebaie; Naglaa Afifi; Sahar A. Ahmed; Mervat E. Behairy; et al. (The Egyptian Journal of Internal Medicine)
Abstract Background The Systemic Lupus Erythematosus Disease Activity-2000 Glucocorticoid Index (SLEDAI-2 KG) accounts for glucocorticoids and possibly promising. The Physician Global Assessment (PGA) is subjective and debatable. Objectives Assessment of the validity of the SLEDAI-2 KG, its association with the PGA, and their potential association with the disease damage. Methods A cross-sectional study included SLE patients managed at 2 tertiary centers in Egypt were conducted. The SLEDAI-2 K was the gold standard score for assessment the disease activity. The SLEDAI-2 KG incorporates glucocorticoids’ dosage through an ordinal weight. The PGA (scale: 0–3) was categorized according to the PGA international standardization consensus in SLE study (PISCOS). Results The study included 608 patients [546 (89.8%) females and [62 (10.2%) males; age at onset: 27.5 ± 8.5 years; age at assessment: 31.4 ± 9.4 years; disease duration: 6.1 ± 5.5 years for females]. The mean SLEDAI-2 K, SLEDAI-2 KG, and PGA was 11.9 ± 9.3, 16 ± 10.5, and 1.2 ± 0.8, respectively. The correlation between both the SLEDAI-2 KG (r: 0.96, p < 0.001) and PGA (r: 0.5, p < 0.001) and SLEDAI-2 K was statistically significant. The association’s strength between both the SLEDAI-2 KG and PGA and SLEDAI-2 K declined among low activity-patients (SLEDAI-2 K < 6) [(r = 0,4; p < 0.001) (r = 0.2; p = 0.02), respectively], and the SLEDAI-2 KG and PGA were not associated in this subgroup (r: 0.07, p = 0.4). The agreement’s strength between the SLEDAI-2 K and PISCOS-PGA was weak (kappa = 0.17, p < 0.001). The SLEDAI-2 K and SLEDAI-2 KG were comparable predictors for damage and the PGA was a weaker predictor. Conclusion The SLEDAI-2 KG and PGA correlated significantly with the SLEDAI-2 K, yet the correlation’s strength declined among low disease activity-patients. The SLEDAI-2 K and SLEDAI-2 KG were comparable predictors for damage.